Particle Number Emission for Periodic Technical Inspection in a Bus Rapid Transit System (2023)
ABSTRACT : This study was carried out under the Climate and Clean Air in Latin American Cities program (CALAC+) and aimed to evaluate the particle-number-based periodic technical inspection (PN-PTI) test in a public bus rapid transport (BRT) system and establish a baseline of PN emission. The PN-PTI test was performed in 1474 buses with emission standards from Euro II to Euro V without diesel particle filter (DPF), Euro V with retrofitted DPF, Euro VI diesel with original engine manufacturer DPF, and compressed natural gas (CNG) fueled. The median PN emission of buses with DPF is below 3000 #/cm3. PN emission limits such as 1,000,000 #/cm3 or 250,000 #/cm3 would allow the approval of vehicles with DPF that are not fully operational. An additional high-idle test is proposed for buses with emissions above 50,000 #/cm3, but below the test approval limit, to detect DPF that may require maintenance. For buses without DPF, which are the majority of the bus fleets in Latin America, the PN emission test can detect and target very-high emitters for developing special policies. CNG buses presented the lowest emissions, likely because of the detection limit of the equipment (23 nm) which cannot detect the large number of particles emitted by these vehicles in the sub-23 nm particle range.